Accretion Product Formation from Self‐ and Cross‐Reactions of RO2 Radicals in the Atmosphere. Issue 14 (5th March 2018) - Berndt, Torsten; Scholz, Wiebke; Mentler, Bernhard; Fischer, Lukas; Herrmann, Hartmut; Kulmala, Markku; Hansel, Armin
Abstract: Hydrocarbons are emitted into the Earth's atmosphere in very large quantities by human and biogenic activities. Their atmospheric oxidation processes almost exclusively yield RO2 radicals as reactive intermediates whose atmospheric fate is not yet fully unraveled. Herein, we show that gas‐phase reactions of two RO2 radicals produce accretion products composed of the carbon backbone of both reactants. The rates for accretion product formation are very high for RO2 radicals bearing functional groups, competing with those of the corresponding reactions with NO and HO2 . This pathway, which has not yet been considered in the modelling of atmospheric processes, can be important, or even dominant, for the fate of RO2 radicals in all areas of the atmosphere. Moreover, the vapor pressure of the formed accretion products can be remarkably low, characterizing them as an effective source for the secondary organic aerosol. Abstract : Rapidly paired up : RO2 radicals in the atmosphere form accretion products according to RO2 +R′O2 →ROOR′+O2 . This pathway is very efficient for functionalized RO2 radicals, reaching rates that surpass those of the competitive NO+RO2 and HO2 +RO2 reactions. Accretion product formation is currently not yet considered in the description of atmospheric oxidation processes.